Collaboration of Local Political Actors in the Advocacy of Kampung Budaya Jalawastu as a Traditional Village - Bambang Hermanto; Lavia Permatasari; Ariful Hikam (ARISTO, 2026)
This study examines the political processes undertaken by local political actors in advocating for Kampung Budaya Jalawastu to be recognized as a Traditional Village in Brebes Regency. It is particularly interesting to explore how local political elites act as decision-makers in addressing administrative, cultural, and political issues while balancing their respective interests. Kampung Budaya Jalawastu is the only hamlet proposed as a Traditional Village in Brebes Regency. The research was conducted over two months (November - December) using a descriptive qualitative method, with data collected through observation, interviews, and document analysis. The data were analyzed descriptively and validated through source and technique triangulation. This study employs elite theory as its analytical framework. The results show that: (1) Local political actors serving as key decision-makers include the Traditional Leader, the Council of Elders, the Village Secretary of Ciseureuh, the Village Head of Ciseureuh, the Head of the Cultural Division at the Brebes Regency Culture and Tourism Office, and the Regent of Brebes. Each actor utilizes their power based on individual interests. (2) Collaboration among the Traditional Leader, the Ciseureuh Village Government, and the Brebes Regency Government has been productive. (3) Advocacy efforts initiated by the Traditional Leader serve as a strategy to maintain their reputation and strengthen ties with the Brebes Regency Government. (4) The advocacy process has significant economic and autonomy implications for the community. This study can inform policies on the development of Traditional Villages, particularly in managing customary forests and communal lands for indigenous communities. It also serves as a reference for formulating Traditional Village governance policies rooted in local wisdom values. Keywords : Local Political Actors; Traditional Village; Collaboration; Kampung Budaya; Jalawastu;